Pengaruh Pemberian Kompres Hangat Terhadap Penurunan Derajat Dismenore Pada Siswi Mas Ushuluddin Kota Singkawang - Ferry Daniel Martinus Sihombing; Dahlan Gunawan; Mutiara Permata Putri (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background:Dysmenorrhea is a gynecological problem defined as cramping pain in the lower abdomen that occurs during menstruation. Management of dysmenorrhea can use non-pharmacological therapy such as warm compresses. Warm compresses can cause blood vessel dilation (vasodilation) so that it can increase blood circulation, relieve ischemia in myometrial cells, decrease myometrial smooth muscle contraction, increase muscle relaxation and reduce pain due to spasm or stiffness. Methods: This research is a quantitative research. This research method is pre-experimental with one group pretest-posttest design. The sampling technique is purposive sampling. The sample in this study were 74 students who experienced dysmenorrhea in January 2022. Data was collected using the Numeric Rating Scale (NRS) dysmenorrhea pain scale observation sheet before (pretest) and after (posttest) warm compresses were given. Data were analyzed using the Wilcoxon Signed Rank Test. Results: After the Wilcoxon Signed Rank Test, the results showed a p-value of 0.000. The p value is smaller than the significant value or Sig. (2-tailed), which is 0.05(p < 0.05) so that H0 is rejected, and Ha is accepted. Conclusion:Based on the results of this study, it can be concluded that there is an effect of giving warm compresses to the decrease in the degree of dysmenorrhea in students of MAS Ushuluddin Singkawang City in 2022.